Minimally Invasive Pedicle Screw Fixation With Indirect Decompression by Ligamentotaxis in Pathological Fractures. Issue 2 (7th April 2020) - Safaee, Michael M; Shah, Vinil; Tenorio, Alexander; Uribe, Juan S; Clark, Aaron J
Abstract: BACKGROUND: The spine is the most common site of bony metastases. Associated pathological fractures can result in pain, neurological deficit, biomechanical instability, and deformity. OBJECTIVE: To present a minimally invasive technique for indirect decompression by ligamentotaxis in pathological fractures. METHODS: A minimally invasive approach was utilized to perform percutaneous pedicle screw fixation in patients who required stabilization for pathological fractures. Preoperative and postoperative computed tomography and magnetic resonance imaging were used to compare spinal canal area and midsagittal canal diameter. RESULTS: Two patients with newly diagnosed pathological fractures underwent minimally invasive treatment. Each presented with minimal epidural disease and a chief complaint of intractable back pain without neurological deficit. They underwent minimally invasive pedicle screw fixation with indirect decompression by ligamentotaxis. In each case, postoperative imaging demonstrated an increase in spinal canal area and midsagittal canal diameter by an independent neuroradiologist. There were no perioperative complications, and each patient was neurologically stable without evidence of hardware failure at their 5- and 6-mo follow-up visits. CONCLUSION: Minimally invasive percutaneous fixation can be used to stabilize pathological fractures and provide indirect decompression by ligamentotaxis. This procedure is associated with minimal blood loss, low morbidity, and rapid initiation of radiation therapy. Only patients with minimal epidural disease, stenosis caused primarily by bony retropulsion, and mild-to-moderate deformity should be considered candidates for this approach.